Análise por geoprocessamento da transmissão da dengue na região metropolitana da Baixada Santista no período de 2012 a 2013 - Moraes, Paulo de (2014)
This study aims to contribute to knowledge about Aedes aegypti in ""metropolitan area of Santos - RMBS."", Based on the spatial analysis of their breeding sites in the insular area of the city of Santos, in the period between 2012 and 2013 proposed the use of techniques spatial data analysis in the surveillance and control of this vector. We used information obtained from the Municipality of Santos reporting through traps placed in blocks and found that transmits dengue mosquitoes. The RMBS comprises the municipalities of Bertioga, Cubatão, Guarujá, Itanhaém, Mongaguá, Peruíbe, Praia Grande, Santos and São Vicente, the last decade has shown an increase of dengue cases. These factors demonstrate the need to describe a detailed study on land management, using as decision aid tool, and geoprocessing.. With an estimated 1,765,277 inhabitants (IBGE 2013), and over the floating population, well above two million, the geographic coverage of 2373 km ² the population is Aedes aegypti, the main transmitter of dengue factor important research in the Region. As a result we expect the temporal and spatial observations of this study projections and results to minimize the epidemic effects.